8-oxoguanine DNA Glycosylase (OGG1) may be a Diagnostic Indicator of Diminished Ovarian Reserve (DOR) - Xia, Jing; Wang, Zehao; Zou, Wen; Jin, Wenyi; Wu, Gengxiang; Yang, Jing (Combinatorial Chemistry & High Throughput Screening, 2023)
Background: Oxidative/antioxidant imbalance is considered a causal cause of diminished ovarian reserve (DOR). 8-oxyguanine DNA glycosylase (OGG1) has been reported to act as an antioxidant by binding non-catalytically to oxidation-induced DNA damage in the promoter region. Objective: This study aimed to evaluate serum OGG1 concentrations in patients with or without DOR and to explore the clinical value of OGG1 as a novel diagnostic indicator for DOR. Methods: Sixty-four women with DOR and seventy-eight women with normal ovarian reserve (NOR) from the reproductive medical center of Renmin Hospital of Wuhan University were included. Enzyme-linked immunosorbent assay (ELISA) kits were used to determine serum OGG1 levels in patients on 2-5 days of the menstrual cycle. Data regarding the enrolled patients were also obtained from the database of the hospital, including age, body mass index (BMI), anti-Müllerian hormone (AMH), etc. Results: OGG1 levels were increased in the DOR group (2.08 ± 0.70 vs 1.46 ± 0.47 nmol/L, P < 0.001) and negatively correlated with AMH levels (Spearman r = -0.586, P < 0.001). After adjusting for age and BMI, a negative association between OGG1 and AMH remained (β = -0.619, P < 0.001). ROC curve analysis showed that a cut-off value of 1.765 nmol/L had an appropriate sensitivity (81.30%) and specificity (76.90%) for discriminating individuals with and without DOR, with the area under the curve (95% CI) of 0.870 (0.814 to 0.926), P < 0.001. Conclusion: We determined that serum OGG1 levels might be suggested as a new diagnostic indicator for DOR.
Keywords: anti-Müllerian hormone